Making legal sense: on jurors’ discovery of objectivity in Argentina’s experience of lay participation in criminal trials - Santiago Abel Amietta (Frontiers in Sociology, 2025)
This article stems from a broader research programme on the recent incorporation of lay decision-makers into the historically professional-only criminal justice systems in Argentina. It draws on ethnographic data from courthouse observations and in-depth interviews with ordinary citizens who served as lay jurors in the mixed tribunal of the Province of Córdoba, the first one in the country to introduce lay participation. The article deploys the conceptual framework of relational legal consciousness to examine jurors’ perceptions of their own role and experiences within the courthouse, vis-à-vis legal professionals and their deployment of legal knowledge. It argues that jurors’ stories of the use of the law, its language and formalities complicate their perception, in conventional and scholarly wisdom, as bearers of emotions and common sense—a realm opposed to the one imagined and reserved for legal professionals, the sphere of uncontaminated application of legal rules and principles. The article contributes in this way to broader debates on the place and impact of lay decision-makers on state judicial adjudication and on the role of emotions and extra-legal reasoning therein.